A systematic review of music interventions for the cognitive and behavioural symptoms of mild cognitive impairment (non-dementia). (July 2022) - Jordan, Catherine; Lawlor, Brian; Loughrey, David
Abstract: Music interventions may represent an effective approach to improving symptoms and delaying progression of MCI to dementia. This review identified nine studies (8 RCT's, 1 observational study) that explored the benefits of music interventions to those with MCI. Studies included five music-playing interventions (sample size (n) ranged from 35 to 201, age ranged from 62 to 94), one music listening intervention (n = 100, mean age = 77 (music intervention) mean age = 76 (dance intervention), one music with movement intervention (n = 16, age range 65–84 years) and two music reminiscence interventions (n = 68; 72, age range = 60–85 years). Only individuals with a clinical diagnosis of MCI were included, no individuals with a diagnosis of dementia were included. Studies were limited due to their sample size, failure to consider confounding variables (i.e. socialization), inconsistency with therapist led sessions, failure to match conditions across interventions, limited follow-up period post-intervention and the tendency to focus on depression exclusively as a measure of behavioural symptoms. Different types of music interventions have differential results on cognitive and behavioural symptoms. The different pattern of brain activation and cognitive abilities which support each type of music activity (e.g. listening vs playing music) may offer some explanation towards these differences. A standardised protocol is needed for each type of music intervention to address how music interventions are studied, taking these limitations into consideration.